Severe postpartum hemorrhage increases risk of posttraumatic stress disorder: a prospective cohort study - Minouk E. van Steijn; Karel W. F. Scheepstra; Tjitske R. Zaat; Diana E. van Rooijen; Claire A. I. Stramrood; Lea M. Dijksman; Arijaan W. Valkenburg-van den Berg; Welmoed Wiltenburg; Joris A. M. van der Post; Miranda Olff; Maria G. van Pampus (Taylor & Francis Group, 2021)
Purpose To evaluate whether severe postpartum hemorrhage (PPH) is a risk factor for posttraumatic stress disorder (PTSD). Severe PPH can be experienced as a traumatic event. PTSD leads to negative mental health effects. Knowing risk factors for PTSD during childbirth offers opportunities for early interventions, which may prevent the development of PTSD. Materials and methods In this prospective study, we compared two groups of participants; women with ≥2000 mL of blood loss (severe PPH, patients) and women with ≤500 mL of blood loss (controls). Participants were screened for PTSD using the PCL-5 four to six weeks after delivery. Positive screening was followed by the CAPS-5 to diagnose PTSD. Results We included 187 PPH patients and 121 controls. Median PCL-5 scores were higher for PPH patients (5.0) than controls (4.0, p = 0.005). Thirteen PPH patients (7.0%) and two controls (1.7%) scored ≥32 on the PCL-5, indicative of probable PTSD (OR 4.45, 95% CI 0.99-20.06, p = 0.035). Significant more PPH patients than controls met criteria for a clinical diagnosis of PTSD on the CAPS-5 (n = 10, 5.6% vs n = 0, 0.0%; p = 0.007). Conclusions There is a significant and clinically relevant increased risk for developing PTSD after severe PPH. Gynecologists and midwives are advised to screen for PTSD at postpartum follow-up visits to prevent long-term negative mental health effects. Clinical Trial Registration NL50273.100.14